The Moslem Community's Perceptions in Using ShopeePay: Fintech as a Mediator for Purchasing MSME's Products - Asep Maulana Rohimat; Helti Nur Aisyiah; Septi Kurnia Prastiwi (UIN Raden Mas Said Surakarta, 2021)
The economic activity carried out by the Moslem community is an interesting thing. Moreover, it is carried out in Indonesia, which is predominantly inhabited by the Moslem population. With these conditions, the Moslem community is considered as one of the most potential market layers, especially in the development of the online MSME business. Moreover, it is supported by growing financial technology (fintech). The purpose of this study was to determine the effect of perceived benefits on purchasing MSME products online with fintech as a mediating variable. This study uses a quantitative approach with the Moslem community in Central Java and Yogyakarta as the object of research. The quantitative approach is used to determine the effect between variables with the help of the SPSS program. The results of this study indicate that the fintech variable has a significant effect on fintech and online purchases, fintech has a significant effect on online purchases, and fintech can mediate the relationship between fintech and online purchases.